The raspberry Gene Is Involved in the Regulation of the Cellular Immune Response in Drosophila melanogaster. - Beáta Kari; Gábor Csordás; Viktor Honti; Gyöngyi Cinege; Michael J Williams; István Andó; Éva Kurucz (PLoS ONE)
Drosophila is an extremely useful model organism for understanding how innate immune mechanisms defend against microbes and parasitoids. Large foreign objects trigger a potent cellular immune response in Drosophila larva. In the case of endoparasitoid wasp eggs, this response includes hemocyte proliferation, lamellocyte differentiation and eventual encapsulation of the egg. The encapsulation reaction involves the attachment and spreading of hemocytes around the egg, which requires cytoskeletal rearrangements, changes in adhesion properties and cell shape, as well as melanization of the capsule. Guanine nucleotide metabolism has an essential role in the regulation of pathways necessary for this encapsulation response. Here, we show that the Drosophila inosine 5'-monophosphate dehydrogenase (IMPDH), encoded by raspberry (ras), is centrally important for a proper cellular immune response against eggs from the parasitoid wasp Leptopilina boulardi. Notably, hemocyte attachment to the egg and subsequent melanization of the capsule are deficient in hypomorphic ras mutant larvae, which results in a compromised cellular immune response and increased survival of the parasitoid.